1981
DOI: 10.1007/bf01256752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin on experimental tumors under different photoperiods and times of administration

Abstract: The effects of melatonin on experimental tumors so far described in the literature are contradictory. This may partially be due to negligence of the importance of environmental photoperiodic conditions and to the time of day of administration. In order to test whether the effect of melatonin on day of administration. In order to test whether the effect of melatonin on tumor growth is dependent on the photoperiod and the time of day of administration, the present experiments were carried out. It appears that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…(6,8,9) A preliminary study demonstrated that pretreatment of rats bearing hepatomas, for two weeks prior to a single dose of radiation administered just prior to lights off, with a non-tumor inhibiting dose of melatonin also given just before lights off, had a marked radiosensitizing effect. Pretreatment of tumor-bearing rats with AM doses of melatonin were ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…(6,8,9) A preliminary study demonstrated that pretreatment of rats bearing hepatomas, for two weeks prior to a single dose of radiation administered just prior to lights off, with a non-tumor inhibiting dose of melatonin also given just before lights off, had a marked radiosensitizing effect. Pretreatment of tumor-bearing rats with AM doses of melatonin were ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Human recombinant IL-2 was supplied by Euro-Cetus (Amsterdam, Holland). MLT was given orally at a dose of 50mg/day in the evening (8.00 p.m.) because of its greater biological activity in the night (Bartsch & Bartsch, 1981). MLT was given every day, starting 7 days before the first IL-2 injection as an induction phase to enhance host biological response to IL-2 (Lissoni et al, 1991).…”
mentioning
confidence: 99%
“…In any case, even though very few randomized studies are available up to now, the clinical results on tumor therapy with pineal hormones are already sufficient to conclude that at least MLT is essential for both palliative and curative therapies of cancer [36]. In fact, it is known since many years that in experimental studies MLT may exert anticancer in vivo activity only it is administered during the dark period of the day, corresponding to the time of its maximal production in normal conditions, and at pharmacological doses [38], corresponding to a dosage of at least 20 mg/day in humans [26]. Moreover, preliminary clinical studies would suggest that the anticancer action of MLT is a dose-dependent phenomenon, and no toxicity occurred even at very high doses greater than 500-1000 mg/day [26].…”
Section: Pineal Endocrine Therapy Of Cancer With Melatonin and Other mentioning
confidence: 99%